Design of Compliant Constant-force Mechanism based on Additional Spring Double-slider Four-bar Mechanism - Zhang Kai; Han Yingge; Li Baokun; Zhang Jie (Jixie chuandong, 2020)
A design method of compliant gripper based on pseudo rigid body model is presented.A compliant clamping mechanism with constant force characteristics is constructed based on the additional spring double-slide four-bar mechanism.The mechanism position analysis model is established and the kinematic statics equation is constructed by using the principle of virtual work.The influence of spring stiffness on the output characteristics of the mechanism is analyzed，and a compliant clamping mechanism design method with constant force characteristics is obtained.Based on the pseudo rigid body model，the additional spring is replaced by a flexible module to obtain a new type of compliant constant force mechanism.The feasibility of establishing compliant constant force mechanism is verified by finite element analysis software.Finally，a new type of compliant constant force gripper with a symmetrical structure is constructed.The design method of the compliant constant force gripper can also be applied to the non-linear stiffness characteristic compliant mechanism design included other types of additional spring mechanisms.